SELF EXECUTING AND NON SELF EXECUTING TREATIES WHAT DOES IT MEAN? - Agusman, Damos Dumoli (Indonesian Journal of International Law, 2014)
This article examines the concepts of self executing treaties and non-self executing treaties. These two concepts are inadvertently related to the dualist and monist theory of international law. They also relate to the question of direct applicability and municipal validity of treaties. This article will show that non-self executing treaties are not always analogous with the concept of dualism under international law. Likewise, treaties might presumably be self executing even in dualist states. It is therefore imperative to acquire an understanding of these two concepts by discerning and analysing them. Such understanding will provide clarity to the question of dualist transformation theory in regards to the municipal validity of treaties. berita politik nasional terkini aims to explore these two concepts, in particular their main ideas, how they relate and attempt to affect the theoretical problem of monism versus dualism with regards to treaties. This article traces the origins of the concept of self-executing treaties by examining it under American law and the European Union legal order as well as relevant decisions by international courts. This Article will then move to examine various scholars suggestion to establish criteria for non-self executing treaties